Linking strategy engagement to strategy execution: a partial least squares (PLS) approach - Chuah, Francis Chin Wei; Teoh, Kenny Guan Cheng (2015)
Given that the strategy execution success rate is relatively low and that prior knowledge about what constitute a successful strategy execution is deem insufficient to explain the real world scenario, this study introduces a new concept “strategy engagement” as one of the facet for successful strategy execution. Using field data collected from 224 middle managers in the service industry in Malaysia, this study examine the effect of strategy engagement on strategy execution by means of PLS-SEM approach. This study also examines the moderating effect of strategy commitment on the relationship between strategy engagement and strategy execution. Outcome of the analysis suggest that strategy engagement is found to have positive significant relationship with strategy execution. The moderating effect, however, is statistically not significant. This study highlights the importance of engagement in strategy execution process and deliberately calls for extensive studies to enhance the knowledge in strategy execution related literature.